ACTIVE SYSTEM MANAGEMENT UNDER UNCERTAINTY - Shakah, G.; Krasnoproshin, V. V.; Valvachev, A. N. (International Journal of Computing, 2014)
The paper describes the use of fuzzy set theory and theory of active systems for constructing systems that manage geographically distributed organizations under uncertainty. Unification algorithms for fuzzy data and their use for choosing management of distant objects are presented.